Ethnopedagogical Approach in Indonesian Language Learning in Elementary Schools - Talita, Jihan Ulfa; Eka Saputra, Erwin (International Journal of Management and Education in Human Development, 2025)
Indonesian language learning in elementary schools has enormous potential in shaping students' character, cultural identity, and language competence. In the context of Indonesia's cultural diversity, an ethnopedagogical approach is a strategic alternative for integrating local wisdom values into the learning process. This article aims to examine the ethnopedagogical approach in Indonesian language learning through a literature review of various research findings and current theories. The study results indicate that ethnopedagogy encourages students to recognise and appreciate local cultures through language as a medium of expression. Indonesian language learning that employs folklore, traditional expressions, and contextualised everyday language practices has been shown to improve literacy skills, positive attitudes toward culture, and active student engagement in learning. This approach aligns with the Independent Curriculum's emphasis on differentiated and contextual learning. However, the implementation of ethnopedagogy still faces challenges, such as limited local culture-based learning resources and teacher competency in developing contextual teaching materials. Therefore, teacher training, policy support, and the development of local culture-based learning resources are needed to support the sustainable implementation of ethnopedagogy in Indonesian language learning in elementary schools.